App Review Prediction Using Machine Learning (Journal of Pharmaceutical Negative Results, 2022)
Millions of users utilize Google Play Store, the company's official android market. It can be utilized to access magazine, gaming, music, movie, and television material, among other things. Users can rate and review apps in the android market after installing them to express their own experiences with them, and this goes both ways in that other user can be inspired by other user’s reviews. Users' experiences usually explain the app's usability, performance, and, in some cases, issues that they have encountered while using it. The goal is to categorise Google’s app evaluations using machine learning approach. The Machine learning approaches are employed to gather element identify things such as emotions, element polarities, and to build a sample utilizing these characteristics, that could then go into a series of procedures including data validation or cleaning, visualization, and finally classification into positive, neutral, and negative sentiments.